Регламентація відповідальності за незаконне позбавлення волі або викрадення людини у законодавстві України та окремих країн Європейського Союзу: порівняльний аспект - Наумова, О.; Naumova, О. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті досліджуються питання особливостей встановлення та диференціації кримінальної відповідальності за незаконне позбавлення волі або викрадення людини у ст. 146 КК України та в законодавстві окремих країн Європейського Союзу. За результатами дослідження визначено основні підходи до законодавчого регулювання кримінальної відповідальності за незаконне позбавлення волі або викрадення людини. Надано характеристику кваліфікуючих та особливо кваліфікуючих ознак цього злочину. На підставі отриманих результатів сформульовано пропозиції щодо вдосконалення ст. 146 КК України. The article considers the establishment and differentiation of criminal responsibility for the illegal imprisonment or kidnapping in the art.146 of the Criminal Code of Ukraine and the legislation of certain EU countries. The author suggested to replace the concept of «the will» by the concept of «freedom» in the title of Section III of the Special Part of Criminal Code of Ukraine. The author substantiated the necessity of some additions to art.146 of Criminal Code of Ukraine concerning qualifying characteristics, namely: illegal imprisonment or kidnapping – committed for the preparation of the crime or facilitating its commission; replace the term «minor» by the term «juvenile», specify the attribute «for a long time» as such, that lasts for more than seven days. It is also necessary to supplement the Section III of the Criminal Code with the Article that would establish responsibility for the forcible removal of a person from the country to the territory of a foreign state (or temporarily occupied territory), or preventing the return of such persons from abroad (from the temporarily occupied territory), in the case when there is no evidence of human trafficking.
Regulation of the Responsibility for theIllegal Imprisonment or Kidnapping in the Legislature of Ukraine and Some Countries of the European Union: a Comparative Aspect.
Keywords: злочини проти волі особи; право на свободу; кримінально-правова охорона; позбавлення волі; викрадення людини; crimes against personal freedom; the right to freedom; the criminal-legal protection; imprisonment; kidnapping